Defending pornography: free speech, sex, and the fight for women's rights - Strossen, Nadine (Scribner, 1995)
This book examines a key question that has divided feminists for decades: is censoring pornography good or bad for women? The book makes a powerful case that increasing government power to censor sexual expression, beyond the limits that the First Amendment sensibly permits (for example, outlawing child pornography) would do more harm than good for women and others who have traditionally been marginalized due to sex or gender. The book explains how the very anti-porn laws pushed by some feminists have led to the censorship of LGBTQ+ and feminist works, and it examines the startling connections between anti-porn feminists and right-wing fundamentalists. The book lays out the multiple current assaults on sexual expression, which continue to come from across the ideological spectrum. It shows that freedom for such expression remains an essential prerequisite for the equality, safety, and dignity of women and sexual/gender minorities.
Keywords: amériques; cours; discipline; droit; droits des femmes*; liberté d'expression; pornographie; premier cycle; régions géographiques; science politique et droit; sex wars; sex1911; thématiques; états-unis